Keanekaragaman tumbuhan pangan dan pemanfaatannya di cagar alam gebugan: potensi sumber daya alam berkelanjutan - Erviani, Eva (Maliki Interdisciplinary Journal, 2025)
This study aims to identify plant species with potential as food sources in the Gebugan Nature Reserve and to assess the level of biodiversity of edible plants in the area. The research method used was field surveys with direct observation and documentation of plants found in the area. The results showed that there are 25 plant species that can be used as food, including tubers, fruits, and leaves, which contain important nutrients such as carbohydrates, vitamin C, and fiber. The biodiversity index of edible plants in the Gebugan Nature Reserve is high, with a Shannon-Wiener diversity index of 3.45, indicating a balanced and stable ecosystem. However, the restriction of local community access to this conservation area may reduce traditional knowledge about plant utilization. Therefore, efforts are needed to document and disseminate this knowledge to the community for sustainable use. This research is expected to serve as a reference for community-based natural resource management and conservation.